Assessment of wind energy potential: a case study - Düzcan, Abdullah; Kara, Yusuf Ali (Bellwether Publishing, Ltd., 2021)
Utilization and investments of wind energy have been speedily rising in the world due to harmful side of the fossil fuels. Assessment of wind energy potential analysis is a must before making investment decision of wind farm. Due to high capacity factor of Aegean Sea, Gökçeada location is chosen for wind energy potential analysis. One year hourly measured wind velocity and direction data supplied by Turkish State Meteorological Service (TSMS) is used to assess the wind potential in the terrain. Two different approaches are used for the assessment, the former employs power-law method for calculating wind velocity field while the latter employs Windsim software based on Computational Fluid Dynamics (CFD) method. After calculating wind velocity field, Weibull method is used for energy analysis in both approaches. Results from each approach are compared. The roughness is attained at only two points that are measurement site and turbine site in power-law method while it is taken into account for the whole domain in CFD method. Besides, unlike CFD method, wind direction is not considered in power-law method. The velocity profile is calculated at the height of 60 m and considered the same everywhere depend on the roughness in power-law method. On the other hand, Windsim calculates velocity profile over the terrain in consideration by solving Reynolds-averaged Navier-Stokes (RANS) equations. In this assessment, seven Vestas V90 2 MW wind turbines are employed. According to the results of power-law method and CFD method, the capacity factor is calculated as 31.67 and 49.5%, respectively. Windsim results indicate that annual energy production (AEP) is 60.2 GWh/y regarding wake loss, and the shape factor ranges from 1.57 to 1.64 whereas scale factor ranges from 9.49 to 10.77 m/s for the locations of turbines. It is strongly advised to build a wind farm in Gökçeada location according to the results from the analysis.
Keywords: CFD; power-law; Wind energy potential in Gökçeada; wind resource potential in Gökçeada; Windsim